Formes, formats, espaces : du sonnet et du tanka chez Jacques Roubaud - Margaux Coquelle-Roëhm (Interfaces)
Poet and mathematician Jacques Roubaud has explored traditional forms such as the sonnet and the tanka, considered as forms in motion. Their geometrical space is arranged according to a relation of proportionality with the page. The potentiality of the form thus informs the format. Roubaud conceives the poem as a shifting “quartet of forms”, of which two are external – spoken and written – and two are internal – “aural” (the inner voice) and “wRitten” (the mental picture of the page) –, and within which deviations can occur. The space of the book is thought of as a hyperpoem in several dimensions, involving the sense of duration in the reader’s memory. The space of the poem therefore exceeds the sole question of format. It forms a volume, a meditative space in which the poem resonates, thus avoiding it being petrified in a purely written form.